(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
In 1981, the metropolitan areas of Montpellier and Chengdu signed the first French-Chinese sister city (SC) agreement. This type of relationship has historically led to what is termed as “decentralized cooperation” (DC), a concept that has been simplified following the enactment of French decentralisation laws in 1992. The primary purpose of sister city agreements was to enable French local administrations to establish formal cooperation and DC projects with foreign local authorities (Tulard 2006: 7-12, 15-55). Regarding SC and DC, the political ambitions of mayors have facilitated the development of a “global village” since the 1950s across various domains, including bilateral economic cooperation, student exchanges, local and international festivals, among others. Consequently, this article examines the role of sister city relationships as a potential means of safeguarding international relations (IR) through a microscale perspective. This study adopts a qualitative approach, drawing on the results of thirty interviews conducted in France and China between 2020 and 2023. In the context of the competition between the “West” and the “Global South,” sister city partnerships are increasingly confronted with crises within a complex global landscape characterized by tensions between deglobalization and European strategies of de-risking. While shifts in the global order remain uncertain, glocal tensions persist, oscillating between cooperation and competition (Bartsch, Wessling 2023: 19-55).